Corticosteroid and Fragrance Allergy Exacerbating Scalp Psoriasis - Jacob, Sharon E. (Matrix Medical Communications, 2014)
Increasing evidence indicates that allergic contact dermatitis can worsen pre-existing psoriasis. The authors highlight a delayed-hypersensitivity reaction to a common psoriasis medication and discuss therapeutic interventions.